An Impedimetric Sensor Based on a Gold Electrode Functionalized with a Thiol Self‐Assembled Monolayer Modified by Terpyridine Ligands for the Detection of Free Gadolinium Ions. Issue 1 (8th October 2014) - Mefteh, Wahid Ben; Touzi, Hassen; Bessueille, François; Chevalier, Yves; Kalfat, Rafik; Jaffrezic‐Renault, Nicole; Gorton, Lo
Abstract An impedimetric method of detection of gadolinium(III) free species has been developed using gold electrodes functionalized by terpyridine ligands. Two chemical attachment processes, on an acidic thiol and on an aminothiol, were designed and the sensitized surfaces were then characterized by chemical analyses, physicochemical and electrochemical methods. The detection of Gd3+ was investigated by impedance spectroscopy. A linear calibration curve was obtained from the variation of the polarization resistance versus pGd3+ in the range 10−8 M to 10−3 M. The impedimetric sensor presented a shelf life of more than six months. Moreover, Gd3+ detection in spiked diluted real urine samples was satisfactorily performed.